2023
DOI: 10.31219/osf.io/8zsc9
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Visual preference for socially relevant spatial relations in humans and monkeys

Nicolas Goupil,
Holly Rayson,
Emilie Serraille
et al.

Abstract: As an extremely relevant social signal, a body/face/gaze facing towards oneself holds an individual’s attention. We asked whether, going beyond an egocentric stance, facingness between others has a similar effect, and why. Using a preferential-looking time paradigm, we showed that human adults looked preferentially at two bodies facing each other, relative to the same bodies presented back-to-back. Moreover, facing dyads were rated higher in social semantic dimensions, showing that facingness adds social value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
2
1
0
Order By: Relevance
“… 18 The same looking-time paradigm was adopted in adult humans and macaques, confirming the different attention driven by the two types of stimuli, and thus, the relevance of such configurations. 20 Those results are compatible with the evidence of perceptual adaptation for efficient processing of seemingly interacting (e.g., face-to-face) bodies. In fact, it has been shown that, in conditions of visual noise, facing bodies are more likely to be detected and recognized than the same two bodies facing away from each other.…”
Section: Introductionsupporting
confidence: 74%
See 2 more Smart Citations
“… 18 The same looking-time paradigm was adopted in adult humans and macaques, confirming the different attention driven by the two types of stimuli, and thus, the relevance of such configurations. 20 Those results are compatible with the evidence of perceptual adaptation for efficient processing of seemingly interacting (e.g., face-to-face) bodies. In fact, it has been shown that, in conditions of visual noise, facing bodies are more likely to be detected and recognized than the same two bodies facing away from each other.…”
Section: Introductionsupporting
confidence: 74%
“…This finding provides evidence that the recognition of face-to-face configuration, likely indicative of interaction, which has been found in infants, adult humans, and adult macaque monkeys, is observed also in birds and does not derive from experience but it is likely to be biologically predisposed in the vertebrate brain. Moreover, given that previous studies in infants never reported a preference for face-to-face stimuli, but only a capacity for discrimination, 18 , 20 the present study is the first report of such an early preference.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation